Children’s lived experience and perceptions of community members’ influence on their schooling: a study in Uganda - Balikoowa, Richard; Ojiambo, Deborah; Emuron, Lydia; Siu, Godfrey; Mbabazi-Mpyangu, Christine; Kikooma, Julius Fred; Mugambwa, Joshua; Nuwagaba, Rachael Daphine; Baluku, Martin M.; Onen, David (Frontiers in Psychology, 2023)
Global and national initiatives have successfully increased access to public education in low-and middle-income countries. However, many students in rural regions in these countries have high rates of absenteeism and drop-out, and low levels of academic engagement. Together, these significantly limit children's academic performance and achievement. One strategy that addresses these barriers seeks to engage members of the wider local community in schools. Most previous research focuses on adults' perspectives even though the potential benefit of community engagement is greatest when learners perceive it to be positive. Past research has also focused on community members structured engagement in activities within schools. This research provides a wider exploration of children's lived experience and perceptions concerning community members' influence on their schooling and learning. The aim was to gain a rich picture of how primary school students in rural Uganda perceive that community members' behavior helps or hinders their education. Qualitative data from students 10 to 13 years of age were collected through individual interviews that used the draw-and-talk technique (n = 20) and four focus group discussions. Seven broad categories of community members' actions were perceived to be positive (conflict resolution; supporting students' physical well-being; encouraging learning and positive behavior; reducing truancy; providing food and financial support; collective community work; and political representation). Four categories of community members' actions were perceived to have a negative influence (creating barriers to attending school; noise and other distractions; insecurity; and theft and vandalism). We conclude that carefully structured community involvement in schooling may improve the emotional and material support that facilitates students' continued school attendance and their motivation for learning. However, we also identify some limits on the role that local communities may be able to play in overcoming the challenges facing education in low-and middle-income countries.